A Knowledge Capabilities Financial Model Based on the Performance of Fashion Enterprises: Micro, Small, and Medium - Windi Novianti; Umi Narimawati; Godwin Ahiase; Panji Pramuditha (Australasian Accounting Business and Finance Journal, 2024)
This study investigates the relationship between financial knowledge capability and MSME performance in West Java, Indonesia, and explores the mediating role of digital marketing and intelligent financial technology. Structural equation modeling was utilized to analyze 375 MSMEs, revealing a significant impact of Financial Knowledge Capability on MSME's performance. Moreover, the study finds that digital marketing and intelligent financial technology mediate this relationship positively, with digital marketing awareness of utilizing intelligent financial technology identified as a key determinant of MSME performance. This research shows that with efforts to improve the role of digital marketing effectively, MSMEs can increase their competitiveness in the market and grow their business significantly. Intelligent Financial Technology allows MSMEs to access financial services such as loans, payments, and investments more easily and quickly. It concludes that specific strategies can be implemented to maximize these contributions.
Keywords: Knowledge Capabilities Financial; Digital Marketing; Intelligent Financial Technology; MSMEs Performance